Forest Diversity and Management 2006
DOI: 10.1007/978-1-4020-5208-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of selective logging and agricultural clearing on forest structure, floristic composition and diversity, and timber tree regeneration in the Ituri Forest, Democratic Republic of Congo

Abstract: Abstract. Mature tropical forests at agricultural frontiers are of global conservation concern as the leading edge of global deforestation. In the Ituri Forest of DRC, as in other tropical forest areas, road creation associated with selective logging results in spontaneous human colonization, leading to the clearing of mature forest for agricultural purposes. Following 1-3 years of cultivation, farmlands are left fallow for periods that may exceed 20 years, resulting in extensive secondary forest areas impacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…It is important to indicate that there were many more trees in the two agroforests reportedly being used in the study area and that only the commonly mentioned used trees are reported here. Generally, the conversion of natural forests to agricultural farmlands involves the removal of a substantial number of forest trees (Makana and Thomas 2006) with subsequent replacement with non-forest trees (Asase et al 2009) In this study, forest species were being replaced with non-forest species such as C. odorata especially in the cocoa agroforest. The replacement of native forest trees with non-forest species in cocoa agroforest is also evident from floristic inventories in Costa Rica (Guiracocha et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to indicate that there were many more trees in the two agroforests reportedly being used in the study area and that only the commonly mentioned used trees are reported here. Generally, the conversion of natural forests to agricultural farmlands involves the removal of a substantial number of forest trees (Makana and Thomas 2006) with subsequent replacement with non-forest trees (Asase et al 2009) In this study, forest species were being replaced with non-forest species such as C. odorata especially in the cocoa agroforest. The replacement of native forest trees with non-forest species in cocoa agroforest is also evident from floristic inventories in Costa Rica (Guiracocha et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several researches indicated the effects of selective logging on flora and fauna diversity; for examples; Asner et al (2006) quantified large-scale changes in canopy damage levels by selective logging in the Brazilian Amazon, revealing that heavy selective logging was often rapidly followed by deforestation. Several studies had reported that selective logging negatively impacted on wildlife habitats (Cloutier et al, 2006;Makana and Thomas, 2006;Arellano et al, 2007;Wells et al, 2007;Laurance et al, 2008). However, it is still unknown to what extent selective logging contributes to deforestation and forest degradation over a longer time scale, as compared with the effects of other demographic and biophysical factors.…”
Section: Introductionmentioning
confidence: 94%
“…Deforestation and forest degradation in the tropics are of major concern to the global carbon budget (e.g., Gullison et al, 2007;Miles and Kapos, 2008;Phelps et al, 2010) and a variety of flora and fauna diversity conservation (e.g., Myers et al, 2000;Cloutier et al, 2006;Makana and Thomas, 2006;Arellano et al, 2007;Wells et al, 2007;Laurance et al, 2008). The patterns and processes of forest cover change have been widely analyzed in many studies using remote sensing data and geographic information systems (GIS) (Ludeke et al, 1990;Lambin, 1997, 2000;Achard et al, 2002;Laurance et al, 2002;Giri et al, 2003;Linkie et al, 2004;Mas et al, 2004;Leimgruber et al, 2005;Armenteras et al, 2006;Etter et al, 2006;Lele and Joshi, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Land disturbances can trigger a sequence of changes in forest structure and composition through time, particularly changes in stem density, richness and species relative frequency (Chazdon et al, 2007;Makana and Thomas, 2006). Although natural disturbances are a persistent driver of tree compositional dynamics, anthropogenic disturbances are increasing at alarming rates, affecting the biodiversity (Novacek and Cleland, 2001).…”
Section: Introductionmentioning
confidence: 99%